Long-term outcome in displaced lateral humeral condyle fractures following internal screw fixation in children - Frongia, Giovanni; Jánosi, Csaba; Mehrabi, Arianeb; Schenk, Jens-Peter; Günther, Patrick (Acta orthopaedica belgica, 2016)
Background : The aim of this study was to investigate the long-term clinical outcome following open reduction and internal screw fixation of displaced lateral condyle fractures (LCFs) of the distal humerus and compare the outcome of primary and secondary LCFs. Methods : The clinical outcome in 31 children (mean age 5.8±2.4 years) operated for primary or secondary LCFs was retrospectively analyzed by standardized clinical examination and compared using the Mayo score, Morger score, and Patients Satisfaction score. Results : The scores did not differ significantly between the primary and secondary displacement groups (Mayo score: 99.3±3.3 vs. 100±0, p=0.852; Morger score: 3.8±0.5 vs. 3.9±0.3, p=0.852; Patients Satisfaction score: 3.7±0.6 vs. 3.9±0.3, p=0.546). Deficits in range of motion and joint axis deviation were minor (< 10°) and no elbow instabilities were observed. Conclusions : Surgical treatment of a secondary displaced LCF with open reduction and internal screw fixation leads to a favorable long-term outcome. The long-term outcome is similar between primary and secondary displaced LCFs.
Gesehen am 11.09.2017